Motor–Language Coupling in Huntington’s Disease Families - Kargieman, Lucila; Herrera, Eduar; Baez, Sandra; García, Adolfo M.; Dottori, Martin; Gelormini, Carlos; Manes, Facundo; Gershanik, Oscar; Ibáñez, Agustín (Frontiers in Aging Neuroscience, 2014)
Traditionally, Huntington’s disease (HD) has been known as a movement disorder, characterized by motor, psychiatric, and cognitive impairments. Recent studies have shown that motor and action language processes are neurally associated. The cognitive mechanisms underlying this interaction have been investigated through the Action Compatibility Effect (ACE) paradigm, which induces a contextual coupling of ongoing motor actions and verbal processing. The present study is the first to use the ACE paradigm to evaluate action-word processing in HD patients and their families. Specifically, we tested three groups: HD patients (HDP), healthy first degree relatives (HDR), and non-relative healthy controls. The results showed that ACE was abolished in HDP as well as HDR, but not in controls. Furthermore, we found that the processing deficits were primarily linguistic, given that they did not correlate with executive function measurements. Our overall results underscore the role of cortico-basal ganglia circuits in action-word processing and indicate that the ACE task is a sensitive and robust early biomarker of HD and familial vulnerability.